A revision of the genus Lycomorphon (Coleoptera: Lycidae) - Nascimento, Elynton Alves Do; Bocakova, Milada (Zootaxa, 2009)
The Neotropical genus Lycomorphon Pic, 1922 is revised. Eleven species are classified in the genus, six of them are redescribed, five species (Lycomorphon brasiliense sp. n., L. amazonicum sp. n., L. bimaculatum sp. n. L. bolivianum sp. n., L. fulvohumeralis sp. n.) are proposed as new to science. Lycomorphon elongaticolle v. diversicolle Pic, 1926 is raised to species status, and Idiopteron irregularis is transferred to the genus Lycomorphon. The new subgenus Spinolycus sg. n. is proposed within Lycomorphon.